Pembangunan Manusia Dan Kinerja Ekonomi Regional Di Indonesia - Aloysius Gunadi Brata (Economic Journal of Emerging Markets, 2002)
Theoretically, there is a two-ways relationship between human development and economic performance. The strength of the relationship also depends on other social and economic variable. The aim of this article is to investigate the relationship in the Indonesia’s regional situation during the economic crisis. This article finds the existence of the links between human development and economic performance.  Keyword: pembangunan manusia,  kinerja ekonomi,  regional, hubungan dua arah .